2022
DOI: 10.3389/fimmu.2022.960570
|View full text |Cite
|
Sign up to set email alerts
|

Versican enrichment predicts poor prognosis and response to adjuvant therapy and immunotherapy in gastric cancer

Abstract: BackgroundIncreasing evidence has revealed an important role of versican (VCAN) on various aspects of cancer progression. Here, we assessed the impact of VCAN expression on prognosis and the response to adjuvant therapy and immunotherapy in patients with gastric cancer (GC).MethodsFour independent cohorts containing 1353 patients with GC, were utilized to investigate the effect of VCAN expression on prognosis and response to adjuvant therapy in GC. Two cohorts treated with immune checkpoint blockades were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Conversely, its expression by stromal cells typically leads to a pro-inflammatory response [18]. In gastric cancer, high expression of VCAN has been associated with increased infiltration of fibroblasts, significant enrichment of stromal-associated signaling pathways and poor prognosis [19]. In hepatocellular carcinoma, VCAN exhibits a strong association with immune checkpoint gene expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, its expression by stromal cells typically leads to a pro-inflammatory response [18]. In gastric cancer, high expression of VCAN has been associated with increased infiltration of fibroblasts, significant enrichment of stromal-associated signaling pathways and poor prognosis [19]. In hepatocellular carcinoma, VCAN exhibits a strong association with immune checkpoint gene expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…HAPLN1 induced multi-drug resistance to bortezomib and ixazomib in patients with multiple myeloma [161]. GC patients with high VCAN are often resistant to immunotherapy [149]; in one study, cervical cancer patients who were resistant to chemotherapy also presented high expression of VCAN [162]. Similarly, elevated RHAMM expression in gliomas is correlated with worse clinical outcomes and higher risk of chemoresistance [163].…”
Section: Deregulated Haims In Solid Tumoursmentioning
confidence: 98%
“…VCAN is widely expressed in the human body and imparts hygroscopic properties to the extracellular matrix (ECM), forming a loosely structured and hydrated matrix which is essential for supporting crucial processes in both development and disease [50]. Accumulation of VCAN in peritumoural stroma was associated with the prognosis of nodenegative breast cancer [142], early stage prostate cancer [143], NSCLC [144], oral squamous cell carcinoma [145], testicular germ cell tumours [146], cervical cancer [147], endometrial cancer [148], and epithelial ovarian cancer [149]. High VCAN expression was reported to be associated with poor prognosis in gastric cancer (GC) patients [149].…”
Section: Deregulated Haims In Solid Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Versican, one of the chondroitin sulfate proteoglycan (CSPG) family members encoded by the VCAN gene, is engaged in cell adhesion, proliferation, migration, and angiogenesis. Song and colleagues demonstrated that high VCAN expression is related to the poor prognosis of patients with gastric cancer, and tumors exhibiting elevated VCAN expression are characterized by microenvironments featuring increased infiltration of CAFs and a notable enrichment of stromal related signaling pathways 226 . Kato and colleagues reported that VCAN secreted by CAFs promotes the carcinogenesis of hepatocellular carcinoma (HCC) cells, suggesting its potential as a novel therapeutic target 227 (Figure 4, right panel).…”
Section: Potential Targets Modulating Functions Of Ecm In Tmementioning
confidence: 99%